# How do you solve -(x+3)+3/4x+5=0?

Feb 12, 2017

See the entire solution process below:

#### Explanation:

First, remove the terms in parenthesis being sure to handle the signs for the individual terms correctly:

$- x - 3 + \frac{3}{4} x + 5 = 0$

Next, multiply each side of the equation by $\textcolor{red}{4}$ to eliminate the fraction while keeping the equation balanced:

$\textcolor{red}{4} \left(- x - 3 + \frac{3}{4} x + 5\right) = \textcolor{red}{4} \times 0$

$\left(\textcolor{red}{4} \times - x\right) - \left(\textcolor{red}{4} \times 3\right) + \left(\textcolor{red}{4} \times \frac{3}{4} x\right) + \left(\textcolor{red}{4} \times 5\right) = 0$

$- 4 x - 12 + \left(\cancel{\textcolor{red}{4}} \times \frac{3}{\textcolor{red}{\cancel{\textcolor{b l a c k}{4}}}} x\right) + 20 = 0$

$- 4 x - 12 + 3 x + 20 = 0$

Then, combine line terms:

$- 4 x + 3 x - 12 + 20 = 0$

$\left(- 4 + 3\right) x + 8 = 0$

$- x + 8 = 0$

Now, add $\textcolor{red}{x}$ to each side of the equation to solve for $x$ while keeping the equation balanced:

$\textcolor{red}{x} - x + 8 = \textcolor{red}{x} + 0$

$0 + 8 = x$

$8 = x$

$x = 8$